1991
DOI: 10.1038/ki.1991.150
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and tubuloglomerular feedback mechanism in chronically salt-loaded spontaneously hypertensive rats

Abstract: Experiments were performed to qualitatively characterize the effects of tubuloglomerular feedback (TGF) inhibition by chronic salt loading on salt sensitivity of blood pressure in spontaneously hypertensive rats (SHR). After two weeks of salt loading, systolic blood pressure (SBP) was significantly exacerbated and plasma volume (PV) was expanded in salt-loaded SHR compared with those in control SHR (SBP: 182 +/- 1 vs. 159 +/- 2 mm Hg; PV: 4.38 +/- 0.06 vs. 4.04 +/- 0.03 ml/100 g body wt, respectively). Plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…In contrast to Dahl SS, we found that SHR fed a normal salt diet have a much greater TGF response than WKY or Dahl SS and that TGF resetting induced by high salt intake was minimal or nonexistent, consistent with previous reports 26,27 . Furthermore, in SHR antagonism of CTGF to the TGF response and its contribution to TGF resetting were also minimal, indicating that a diminished CTGF may at least partially explain the enhancement in TGF and reduced TGF resetting.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to Dahl SS, we found that SHR fed a normal salt diet have a much greater TGF response than WKY or Dahl SS and that TGF resetting induced by high salt intake was minimal or nonexistent, consistent with previous reports 26,27 . Furthermore, in SHR antagonism of CTGF to the TGF response and its contribution to TGF resetting were also minimal, indicating that a diminished CTGF may at least partially explain the enhancement in TGF and reduced TGF resetting.…”
Section: Discussionsupporting
confidence: 92%
“…Ang II is the principal modulator known for strengthening the TGF response (13,14), and macula densa nitric oxide is the principal modulator known for weakening the TGF response (15)(16)(17)(18). Nonetheless, there is precedent for dietary salt to lack influence over the range of the TGF response evoked by perfusing Henle's loop with artificial tubular fluid (ATF) (11,19). Furthermore, the present data regarding the TGF response are in keeping with expectations inasmuch as angiotensin receptor blockade reduced the range of the TGF response by about half (Table 2 and Figure 1).…”
Section: Discussionsupporting
confidence: 77%
“…Supplemental dietary Cl Ϫ that induces chloruresis induces an increased delivery of Cl Ϫ to the macula densa of the thick ascending limb of the renal tubule, and that increased delivery can entrain constriction of the afferent arteriole as part of the normal tubuloglomerular feedback response (34). In the SHR an exaggeration of this response has been observed (35), even into adulthood (36,37), and proposed as a mechanism of hypertension (35,37,38). In the SHRSP, a Cl Ϫ -mediated constriction of the renal afferent arteriole that further narrows it might then exacerbate hypertension.…”
Section: Discussionmentioning
confidence: 99%